1997
DOI: 10.1159/000023835
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Nitric Oxide in IgE-Mediated Allergic Cutaneous Reaction in Mice

Abstract: The role of nitric oxide (NO) in the development of allergic cutaneous reactions in mice was investigated. A biphasic cutaneous reaction composed of an immediate-phase edema and a late-phase edema was evoked by epicutaneous application of 2,4-dinitrofluorobenzene on the ear of mice passively sensitized with mouse anti-dinitrophenol monoclonal IgE. Two NO synthase inhibitors, L-NG-nitroarginine methyl ester (L-NAME) and NG-monomethyl-L-arginine, significantly inhibited both phases of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It has also been reported that an iNOS inhibitor exerted a suppressive effect on the CHS response to 2,4,6-trinitrochlorobenzene (TNCB) (Musoh et al, 1998), although this effect was limited to the first few hours of the response, and neither NO production, NO-expressing cells, nor NOS isoenzymes were identified. Thus, the mode of action of iNOS in CHS remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that an iNOS inhibitor exerted a suppressive effect on the CHS response to 2,4,6-trinitrochlorobenzene (TNCB) (Musoh et al, 1998), although this effect was limited to the first few hours of the response, and neither NO production, NO-expressing cells, nor NOS isoenzymes were identified. Thus, the mode of action of iNOS in CHS remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition by WEB2086 also may support participation of PAF in the induction of the LPR. Recently, it has been known the involvement of nitric oxide (NO) in the biphasic cutaneous reactions [21] and of tumor necrosis factor-a (TNF-a) and interleukin-1b (IL-1b) in the LPR [12,22]. Although interaction between PAF and NO on mast cells is unknown, several PAF antagonists suppress the induction of NO synthase in macrophages [23].…”
Section: S Yamaguchi Et Almentioning
confidence: 99%